2013
DOI: 10.1371/journal.pone.0072182
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint Features of Genomic Rearrangements in Neuroblastoma with Unbalanced Translocations and Chromothripsis

Abstract: Neuroblastoma is a pediatric cancer of the peripheral nervous system in which structural chromosome aberrations are emblematic of aggressive tumors. In this study, we performed an in-depth analysis of somatic rearrangements in two neuroblastoma cell lines and two primary tumors using paired-end sequencing of mate-pair libraries and RNA-seq. The cell lines presented with typical genetic alterations of neuroblastoma and the two tumors belong to the group of neuroblastoma exhibiting a profile of chromothripsis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…The discovery of such a pattern of complex interchromosomal rearrangements, including joining deletions, duplications, and inversions, was made by combining single nucleotide polymorphism (SNP) assays and next-generation paired-end sequencing. Similar cataclysmic phenomenons have been documented in various cancers such as medulloblastoma, neuroblastoma, myeloma, melanoma, colorectal cancers, prostatic cancers, and hematologic malignancies (13)(14)(15)(16)(17)(18). Recently, a survey of 4,934 cancers indicated that chromothripsis was found in 5% of all samples, with incidences ranging from 0 in head carcinoma to 16% in glioblastoma (19).…”
Section: Discovery Of Chromothripsis In Cancers and Congenital Diseasessupporting
confidence: 61%
“…The discovery of such a pattern of complex interchromosomal rearrangements, including joining deletions, duplications, and inversions, was made by combining single nucleotide polymorphism (SNP) assays and next-generation paired-end sequencing. Similar cataclysmic phenomenons have been documented in various cancers such as medulloblastoma, neuroblastoma, myeloma, melanoma, colorectal cancers, prostatic cancers, and hematologic malignancies (13)(14)(15)(16)(17)(18). Recently, a survey of 4,934 cancers indicated that chromothripsis was found in 5% of all samples, with incidences ranging from 0 in head carcinoma to 16% in glioblastoma (19).…”
Section: Discovery Of Chromothripsis In Cancers and Congenital Diseasessupporting
confidence: 61%
“…The breakpoints on chromosome 9 are not the same, but this raises the possibility that the PTPRD locus is a chromothripsis hotspot. Deletions and duplications within PTPRD are among the most common SVs in chromothriptic neuroblastoma genomes [94,95]. …”
Section: Sv Hotspotsmentioning
confidence: 99%
“…Indeed, recurrent structural alterations of the ODZ3 , PTPRD and CSMD1 genes were observed, which play a role in neuronal growth cone stabilization. Structural rearrangements were also shown to occur within NBAS in the vicinity of MYCN …”
Section: Somatic Genetic Alterations In Nb Determined By Next‐generatmentioning
confidence: 99%
“…Although in a subsequent study some cases also presented a high number of chromosome breakpoints, the many complex copy‐number states and retention of heterozygosity in lower copy‐number regions were not believed to suggest a chromothripsis‐linked origin of these alterations. Further evidence of the genomic structure of rearrangements, including those observed in association with chromothripsis, has been provided by whole‐genome sequencing of two cell lines and two NBs, the latter with a genomic chromothripsis profile . Analysis of 59 breakpoint junctions of both chromothripsis‐associated and ‐nonassociated rearrangements at a single base resolution revealed frequent microhomologies (40/59) at the junction, as well as complex rearrangements with templated insertions of fragments of nearby sequences in 4/59 cases.…”
Section: Somatic Genetic Alterations In Nb Determined By Next‐generatmentioning
confidence: 99%